Modelagem numérica do escoamento em válvulas de compressores alternativos pelo método da fronteira imersa com refinamento adaptativo - Barbi, Franco [UNESP] (2012)
In refrigeration compressors, the suction and discharge valves are responsible for the retention and passage of the refrigerant fluid from the suction chamber to the cylinder, and from the cylinder to the discharge chamber. Valve system designers seek for valves with small overall flow pressure drop in order to increase the compressor efficiency. As the opening and closing of the valves are caused by the forces produced by the refrigerant flow, the understanding of the flow through the valve is of fundamental importance in order to enhance the efficiency of the valve system. The numerical simulation of the flow is an efficient method to perform this task. Due to the complex geometry usually found in this type of valve, simplified geometries have been used to represent the valve, particularly the radial diffuser geometry. The Immersed Boundary method is very attractive when it comes to complex geometries and fluid-structure interaction, for it allows the simulation of fluid flow past complex geometries, with boundary movement, without complicating the mesh generation process. In the present work, the Multi-Direct Forcing introduced by Wang (2007) is used for the rigid body force calculations. The incompressible, viscous flow is solved by the AMR3D (Adaptive Mesh Refinement 3D) which contains a semi-implicit time discretization scheme of second order and a projection method for the pressure-velocity coupling. The mesh generated by the code consists in sequences of nested, progressive finer rectangular grid patches, which dynamically adapts to the flows vorticity field and the presence of an immersed boundary. The numerical method is validated with experimental data obtained for the flow through the radial diffuser's geometry. A model that represents well the real geometry of the real valve is proposed, with angular movement imposed for valve opening and closing simulation. Results show that the ...